Increased angiogenesis and lymphangiogenesis in inflammatory versus noninflammatory breast cancer by real-time reverse transcriptase-PCR gene expression quantification - Van der Auwera, Ilse; Van Laere, Steven J; Van den Eynden, Gert G; Benoy, Ina; van Dam, Peter; Colpaert, Cecile G; Fox, Stephen B; Turley, Helen; Harris, Adrian L; Van Marck, Eric A; Vermeulen, Peter B; Dirix, Luc Y (Clinical cancer research, 2004)
Inflammatory breast cancer is a distinct and aggressive form of locally advanced breast cancer with unique clinical and pathological features. Recently, histologic evidence of intense angiogenesis was found in inflammatory breast cancer specimens. The aim of this study was to confirm the angiogenic phenotype of inflammatory breast cancer and to investigate its potential to induce lymphangiogenesis. Real-time quantitative reverse transcriptase-PCR was used to measure levels of mRNA of tumor angiogenesis and lymphangiogenesis-related factors [vascular endothelial growth factor (VEGF)-A, VEGF-C, VEGF-D, Flt-1, KDR, Flt-4, Ang-1, Ang-2, Tie-1, Tie-2, cyclooxygenase-2, fibroblast growth factor-2 (FGF-2), Egr-1, Prox-1, and LYVE-1] in tumor specimens of 16 inflammatory breast cancer and 20 noninflammatory breast cancer patients. Tissue microarray technology and immunohistochemistry were used to study differential protein expression of some of the angiogenic factors in inflammatory breast cancer and noninflammatory breast cancer. Active lymphangiogenesis was further assessed by measuring lymphatic endothelial cell proliferation. Inflammatory breast cancer specimens had significantly higher mRNA expression levels than noninflammatory breast cancer specimens of the following genes: KDR (P = 0.033), Ang-1, (P = 0.0001), Tie-1 (P = 0.001), Tie-2 (P = 0.001), FGF-2 (P = 0.002), VEGF-C (P = 0.001), VEGF-D (P = 0.012), Flt-4 (P = 0.001), Prox-1 (P = 0.005), and LYVE-1 (P = 0.013). High mRNA levels of FGF-2 and cyclooxygenase-2 corresponded to increased protein expression by immunohistochemistry. Inflammatory breast cancer specimens contained significantly higher fractions of proliferating lymphatic endothelial cells than noninflammatory breast cancer specimens (P = 0.033). Using real-time quantitative reverse transcriptase-PCR and immunohistochemistry, we confirmed the intense angiogenic activity in inflammatory breast cancer and demonstrated the presence of active lymphangiogenesis in inflammatory breast cancer. This may help explain the high metastatic potential of inflammatory breast cancer by lymphatic and hematogenous route. Both pathways are potential targets for the treatment of inflammatory breast cancer.